Revolutionary IoT Cold Chain Monitoring for Freshness Preservation - R, Sarankumar; M , Chairman; S , Sooriya Prabha; B, Manojkumar (International Journal of Basic and Applied Sciences, 2025)
Cold chain development is essential for preserving perishable agricultural products and reducing post-harvest losses. An estimated one-third of the food produced for human consumption is lost or wasted worldwide, resulting in significant negative environmental and economic impacts. This article highlights cutting-edge technologies that improve cold chain efficiency, focusing on key elements of a successful cold chain, including distribution, transportation, and storage. A properly established cold chain can enhance food security, lower waste, and promote sustainable agricultural practices by guaranteeing the integrity of food products from farm to table.
Keywords: Blynk IoT, ESP32microcontroller, Humidifier, Perishable Goods, Real-Time Monitoring, Sensors, Supply Chain Management, ThingSpeak Cloud platform